A phantom study: Should 124I‐mIBG PET/CT replace 123I‐mIBG SPECT/CT?. Issue 5 (17th April 2017) - Beijst, Casper; de Keizer, Bart; Lam, Marnix G.E.H.; Janssens, Geert O.; Tytgat, Godelieve A.M.; de Jong, Hugo W.A.M.
Abstract : Purpose: The isotope 123 I is commonly labeled with meta‐iodobenzylguanidine (mIBG) for imaging of neuroendocrine tumors, such as pheochromocytomas and neuroblastomas. 123 I‐mIBG SPECT/CT imaging is performed for staging, follow‐up and selection of patients for treatment with 131 I mIBG. As an alternative to 123 I, 124 I‐mIBG PET/CT may be used, potentially taking advantage of the superior PET image quality. The purpose of this study was to investigate whether 124 I PET/CT improves image quality as compared with 123 I SPECT/CT for equal patient effective radiation dose (in mSv). Methods: Phantom measurements were performed using the NEMA‐2007 image quality phantom. SPECT and PET reconstruction settings were used with and without time‐of‐flight (TOF) and point‐spread‐function (PSF) modeling. As a measure of image quality, the contrast‐to‐noise ratio (CNR) was calculated. The ratio of the 123 I to 124 I activity concentration was determined at which the contrast‐to‐noise ratio was equal for both modalities. This metric was defined as the contrast equivalent activity ratio (CEAR). Results: CEARs of 47.7, 25.6, 23.1, 14.6, 10.0, and 9.1 were obtained for a TOF and PSF modeled 124 I reconstruction method and an attenuation and scatter‐corrected 123 I reconstruction method for sphere sizes of 10 to 37 mm, respectively. As the effective radiation dose of 124 I‐mIBG is higher than of 123 I‐mIBG (in mSv/MBq), an equal effective dose corresponds to a CEAR of 5 to 10. Therefore, CEARs higher than 5 to 10 indicate that 124 I PET/CT outperforms 123 I SPECT/CT in the sense of image quality for equal patient effective radiation dose. Conclusion: The CEAR is much larger than a factor of 5 to 10 (needed for equal patient effective radiation dose) for most of the reconstruction methods and sphere sizes. Therefore, 124 I‐mIBG PET/CT is expected to improve image quality and/or may be used to reduce effective patient dose as compared with 123 I‐mIBG SPECT/CT.